MENGURAI MASALAH PENGEMBANGAN SUKUK KORPORASI INDONESIA MENGGUNAKAN ANALYTIC NETWORK PROCESS - Nila Dewi (Tazkia Islamic Finance and Business Review, 2011)
Sukuk as an instrument of Islamic finance has created the competitive advantages for the practitioners of Islamic finance, which it can contribute of funding mobilization in economic development. Although in size of issuance and emission growing rapidly, but the growth of sukuk has slow moving. These causes are consist of 1) emiten problem: lack of commitment, understanding, averse to risk, and low of corporate rating; 2) investor problem: lack of knowledge, averse to risk, diversification, profitoriented/floating majority; 3) supporting problem: incentive, taxation, socialization, understanding of underwriter; 4) market problem: conventional dominant, lack of instruments, low of size of issuance, liquidity of secondary market. Therefore, this study try to identifies some causes, factors and hindrances the development of corporate sukuk in Indonesia. The results show that the primary problems come from: 1) lack of understanding (emiten); liquidity of secondary market (market); 3) lack of knowledge (investor); 4) incentive (supporting); 5) low of size of issuance. The primary solutions are: 1) intensive socialization; 2) encouragement to state owned corporation; 3) taxation regulation; 4) product innovation; 5) incentive. Furthermore, the levels of agreement among respondents (Kendall’s coefficient) conclude that practitioners show higher rater agreement than that of experts. Therefore, in applying of sukuk, appraisal and opinion of practitioners can be used in considering.JEL Classification : C14, G39Keywords : ANP, Sukuk Corporate